The Role of Technology in English Classrooms: Exploring Teachers’ and Students' Perspective - Resti Resti; Aser Yodika; Dian Shinta Sari; Maliqul Hafis; Nofry Cristina; Nurul Hafizah; Oktapia Maharani; Oktavianus Kampoan; Patricia Dela Natali; Paulus Kindi; Pito Pabayo Putra; Ridho Firmansyah; Sania Gusmiarni; Abang Ismail (Universitas PGRI Pontianak, 2023)
This study aims to explore the role of technology in English language learning based on the perspectives of teachers and students at SMA Negeri 2 Selakau. The research approach used is descriptive qualitative with data triangulation techniques through classroom observation, semi-structured interviews, and documentation. The results showed that teachers used various technological tools such as PowerPoint, learning videos, interactive applications (Kahoot, Quizizz), and digital dictionaries to increase students' engagement and understanding. Students show higher interest and motivation when learning using technology, especially through audio-visual media and video-based assignments. However, some challenges were also found, such as limited infrastructure, low digital literacy, and technical glitches during learning. Teachers' and students' perspectives generally indicate that technology has great potential in improving the effectiveness of English language learning, but it needs to be supported by adequate training and facilities. This research makes a contextual contribution to the understanding of technology integration in language education in rural Indonesia. In conclusion, the integration of technology in English classrooms, while beneficial and motivating for both teachers and students, requires adequate support, training, and infrastructure to ensure its sustainable and effective implementation in rural educational contexts.